Testing Long-Run Monetary Neutrality in Malaysia: Revisiting Divisia Money - Puah, Chin-Hong; Muzafar Shah, Habibullah; Lau, Evan; Shazali, Abu Mansor (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study re-examines the long-run neutrality (LRN) of money on real output in Malaysia using quarterly Divisia money data from 1981:1 to 2004:4 based on Fisher and Seater’s (1993) nonstructural reduced form bivariate ARIMA model. Special attention has been given in identifying the number of unit root and cointegrating vector, as a meaningful LRN test is critically depends on such properties. Empirical results indicate that LRN is deviated from Malaysian economy when Divisia money is used. In particular, Divisia monetary expansion seems to have long-run positive effect on real output in Malaysia.